Psychological Solidity and its Relationship to Academic Procrastination among University Students - a Field Study at University of Setif 2 -- - بن عمارة, سعيدة (Milev Journal of Research and Studies, 2023)
The study aimed to identify the nature of the relationship between psychological solidity in its different dimensions (commitment, control, and challenge) and academic procrastination among the University of Setif 2. The descriptive approach was used, while the study sample consisted of (120) students from the Department of Psychology and Education Sciences and orthophony at the University of Setif 2, they answered on the scale of the psychological solidity prepared by Al Akashee, and a scale for academic procrastination from the preparation of Al Attabe. The results showed that the level of psychological solidity among students was generally high, while the level of academic procrastination was average, and the results also indicated that there is an inverse relationship between psychological solidity (with its various dimensions) and the academic procrastination of students.